Regenerative benefits of using growth factors in treatment of periodontal defects: A systematic review and meta‐analysis with Trial Sequential Analysis on preclinical studies. (14th September 2021) - Farimani, Zeinab; Shamshiri, Ahmad Reza; Asl roosta, Hoori; Akbari, Solmaz; Bohlouli, Mahboubeh
Abstract: The ultimate goal in periodontal treatments is to achieve a functional and anatomical regeneration of the lost tissues. Numerous studies have in some way illustrated the beneficial effects of biologic modifiers in this process, yet they are subject to a rather large degree of diversity in their results. Thanks to the promising outcomes of bioengineering techniques in the field of periodontal regeneration, this systematic review aims to evaluate the effect of various biologic modifiers used in periodontal defects of animal models. Electronic databases (Medline, Scopus, Embase, Web of Science, and Google Scholar) were searched (March 2010–December 2020) for every study that used biomolecules for regeneration of periodontal osseous defects in animal models. Regenerated bone height or area, new cementum, new connective tissues, new regenerated periodontal ligament and the dimensions of epithelial attachment (either in mm/mm 2 or percentage) were the investigated outcomes. The risk of bias of the included studies was assessed using the SYRCLE tool. In closing, there was a meta‐analysis carried out on the outcomes of interest. Trial Sequential Analysis was also carried out to figure out the power of meta‐analytic outcomes. From 1995 studies which were found in the initial search, 34 studies were included in this review, and 20 of them were selected for the meta‐analysis. The eligible studies were categorized according to the morphology of the experimental periodontal defects as one‐, two‐, and three‐wall intrabony defects; furcation defects, and recession‐type defects. The most studied biomolecules were rhFGF‐2, rhGDF‐5, platelet‐derived growth factor, bone morphogenetic protein‐2, and enamel matrix derivative (EMD). Based on the meta‐analysis findings, combined application of biomolecules with regenerative treatments could improve new bone and cementum formation near 1 mm when compared to the control groups in one, two and three‐wall intrabony defect models ( p < 0.001). In furcation grade II defect, the addition of biomolecules was observed to enhance bone area gain and cementum height regeneration up to almost 2 mm ( p < 0.001). Trial Sequential Analysis results confirmed the significant effect in the aforementioned meta‐analyses. In cases of the buccal recession model, the application of rhFGF‐2 and rhGDF‐5 decreased the dimension of epithelial attachments besides regenerative advantages on bone and cementum formation, but EMD deposition exerted no inhibitory effect on epithelial down‐growth. Application of biologic modifiers especially FGF‐2 and GDF‐5, could positively improve the regeneration of periodontal tissues, particularly cementum and bone in animal models. Trial Sequential Analysis confirmed the results but the power of the evidences was high just in some subgroup meta‐analyses, like bone and cementum regeneration in furcation grade II model and cementum regeneration in one‐wall intrabony defects. The outcomes of this study can potentially endow clinicians with guidelines for the appropriate application of growth factors in periodontal regenerative therapies.